Penggunaan Metode Diskusi Sebagai Upaya Meningkatkan Hasil Belajar Bahasa Indonesia Peserta Didik di Kelas I SDN 58/X Teluk Majelis Semester Ganjil Tahun Ajaran 2021/2022 - Rosianty Rosianty (Departement of Mathematics Education, 2022)
This study aims to describe and obtain information on improving Indonesian language learning outcomes through the discussion method. This research is a classroom action research consisting of two cycles, each cycle consisting of two meetings. Each meeting consists of four stages, namely planning, implementation, observation and reflection. The subjects of this study were the first grade students of SDN 58/X Teluk Majelis, totaling 21 people. This research was conducted in the odd semester of the 2021/2022 academic year. Data collection techniques using tests, observations, and documentation. Data were analyzed using percentages. The results of the study indicate that the discussion method can improve the learning outcomes of first grade Indonesian students at SDN 58/X Teluk Majelis by giving rewards.